Determining Length of Breastfeeding Exclusivity: Validity of Maternal Report 2 Years after Birth. (May 2014) - Burnham, Laura; Buczek, Magdalena; Braun, Natalie; Feldman-Winter, Lori; Chen, Ning; Merewood, Anne
Background: Infant feeding data are often collected retrospectively through maternal report. Validation studies show that maternal report of initiation and duration of any breastfeeding is accurate but that report of duration of exclusive breastfeeding may be less accurate. Objective: This study aimed to compare infant feeding data collected longitudinally throughout the first 6 months of life with maternal report of duration of exclusive breastfeeding collected 2 years postpartum. Methods: Infant feeding data were collected prospectively throughout the first 6 months of life from medical records and maternal report, including maternal 24-hour recall. At 2 years postpartum, we asked mothers of these same infants how long they exclusively breastfed their infants. Their responses were compared to the prospectively collected data. Simple and multiple linear regressions tested for any significant predictors of the difference between the prospectively collected data and maternal report at 2 years. Results: Of the 292 mothers included in the final analysis, only 88 (30.1%) mothers reported a duration of exclusive breastfeeding at 2 years postpartum that matched the prospectively collected data. Sixty-four women reported exclusively breastfeeding for the recommended 6 months (21.9%), but according to the prospectively collected data, only 2 women (0.7%) breastfed exclusively through 6 months. The median difference between the prospectively collected data and maternal report at 2 years was 1 month (IQR, 0-4). Conclusion: In this sample of mothers, report of exclusive breastfeeding practices 2 years after birth was often inaccurate and mothers tended to overestimate duration.